MAKNA PENYULUHAN HUKUM SEHUBUNGAN DENGAN PEMBUATAN AKTA OLEH NOTARIS DI KABUPATEN KENDAL - Muhammad Ali Alala Mafing; Munsyarif Abdul Chalim (Jurnal Akta, 2017)
This research will discuss a problem of notary in interpreting Legal Counceling connect to the Deed Creation by Notary in Kendal Regency (Article 15 paragraph 2 letter e of Act Number 2 of 2014 concerning Notary Position) including where the Notary is not performing properly the authority contained in the law of Deed making.This research uses method of yuridic sociologic. The technique of data collecting is conducted with library research including primary and secondary data. The result shows that: (1) notary only provide a counceling to client and do not provide legal counceling thoroughly to the public (2) the extention material provided is limited about the making of deed when client comes. (3) notary only use the article pasively. It means that if the client does not come then the notary does not provide legal counceling.The conclusion is Notary should interprets the article and implements it activelydeal with its authority in giving legal counceling. So the purpose of the constitution is done well.Keywords : notary, legal counceling, the deed